Critical gap analysis of merging sections at Kuala Lumpur middle ring road - Sanik, M. E.; Rahimi, N. F. L.; Hamid, N. B.; M. Nor, A. H.; Prasetijo, J.; Razali, N. F. (Penerbit UTeM, 2017)
At merging sections, drivers normally slow down and sometimes need to stop while seeking a suitable gap before merging with the mainstream. Thus, there will always be several observed rejected gaps and an accepted gap which can be used to determine the smallest average gap, so-called critical gap. This study was carried out to determine critical gap values at selected merging sections at the Jalan Tun Razak and the DUKE Expressway uses the Maximum Likelihood method. Data were collected by using videotaping method and the gap acceptance data were extracted for analysis. A gap acceptance event at highway merging sections in this study was redefined due to unavailability of stopping vehicles at the ramp junction. Therefore, the gap data were estimated starting from a ramp’s vehicle passing the end of gore marking to where it merges with the mainstream. The analysis of the critical gap takes into consideration accepted gaps greater than 5 seconds to avoid forced entry due to lead impedance of successive vehicles on mainstream. The critical gap values obtained in this study, according to vehicle classification were ranged between 4.5 to 5.0 seconds, which are slightly smaller if compared to critical gap values for particularly left turn from minor movement at priority junction of the Arahan Teknik (Jalan) 11/87 and the United States Highway Capacity Manual 2000. The findings shall help to study driving behavior of local drivers, especially at priority control facilities such as merging sections.